CMR feature tracking cloud assess right ventricular functional reserve with pulmonary arterial hypertension. (13th July 2021) - Sato, H; Someya, Y; Nishiyama, M; Satoh, W; Kumasaka, K; Shindoh, C; Ota, H; Ueda, T; Kawashima, R; Miura, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): JSPS KAKENHI, Grant-in-Aid for Early-Career Scientists. Background: Pulmonary arterial hypertension (PAH) remains a fatal disorder characterized by elevated pulmonary arterial pressure. Survival of the patients with PAH is determined from right ventricular (RV) function. CMR has become an attractive modality for following up and providing prognosis in such patients, and CMR feature tracking has been used as a newer useful parameter to assess RV function. However, it has not yet been determined whether CMR feature tracking can assess RV functional reserve in patients with PAH. Purpose: We investigated whether CMR feature tracking can estimate RV functional reserve using a rat model with PAH. Methods: Rats were received injections with monocrotaline (MCT-rats, n = 19) or solvent (Ctr-rats, n = 5). Four weeks after the injections, we performed CMR on 7-T MRI scanner and imaged retrospective ECG-gated cine MR (16 phases/beat). RV ejection fraction (RVEF) and RV strain were analyzed before and after addition of 0.5∼3 nmol endothelin-1 (ET-1). After the measurements, we dissected trabeculae (length = 1.45 ± 0.07 mm, width = 334 ± 27 µm, thickness = 114 ± 6 µm) from the RVs of rat hearts. Trabeculae were electrically stimulated with 2-s intervals at extracellular Ca2+ of 0.7 and 2.0 mmol/L (24°C). Force and maximum dF/dt (dF/dtmax) were then measured using a silicon strain gauge in the absence and presence of 0.1 µM ET-1. Results: MCT-rats showed higher systolic RV pressure (RVP), lower RVEF, and lower RV global longitudinal strain (RVGLS) in CMR imaging and showed lower developed force and lower dF/dtmax in their trabeculae. Correlation between RVGLS and dF/dtmax was higher (r = 0.53, p < 0.05) than that between RVEF and dF/dtmax (r = 0.24). In 5 MCT-rats with preserved RVEF (>50%), RVGLS had already been reduced, suggesting that RVGLS is reduced earlier than RVEF. ET-1 increased developed force and dF/dtmax in trabeculae from MCT-rats (12.2 ± 5.7 to 17.4 ± 3.1 mN/mm2 and 0.08 ± 0.03 to 0.14 ± 0.06 mN/mm2/sec, respectively, n = 6), and ET-1 also increased RVP in MCT-rats and Ctr-rats (49.0 ± 19.3 to 59.7 ± 16.8 mmHg in MCT-rats, n = 6, 17.3 ± 7.5 to 20.4 ± 7.8 mmHg in Ctr-rats, n = 2). According to RV global circumferential strain (RVGCS) and RVEF, we could divide MCT-rats into three groups as follows: MCT-rats with reduced-RVGCS (> -20%)/preserved-RVEF (> 50%), MCT-rats with increased-RVGCS (< -30%)/preserved-RVEF and MCT-rats with reduced-RVGCS/reduced-RVEF. ET-1 reduced RVGCS in MCT-rats with reduced-RVGCS/preserved-RVEF, while ET-1 did not change RVGCS in MCT-rats with increased-RVGCS/preserved-RVEF. MCT-rats with reduced-RVGCS/reduced-RVEF died after injection of ET-1. In Ctr-rats, ET-1 did not change RVGCS and RVEF. These results suggest that RVGCS can be useful to assess RV functional reserve. Conclusion: CMR feature tracking can estimate RV functional reserve earlier and more accurately than RVEF in rats with PAH. RV strain may become an important parameter to assess RV functional reserve in patients with PAH.